Dutch youth’s smoking behaviour during a partial covid-19 lockdown - Tessa R.D. van Deelen; Bas van den Putte; Anton E. Kunst; Mirte A. G. Kuipers (Journal of Public Health Research, 2021)
Previous research found that adult smokers increased their smoking in response to the Covid-19 lockdown in spring 2020. This study explored changes in youth’s smoking during, compared to before, the partial lockdown in the Netherlands in a cross-sectional sample of 287 adolescents. Smoking prevalence increased from 4.5% to 5.2%. Cigarette consumption remained the same on school days and increased with +1.9 cigarettes per weekend day. The largest increase in cigarette consumption on weekend days was observed for adolescents who 1) did not consider smoking a risk factor for contracting Covid-19 (+4.5), 2) had smoking siblings (+4.1), and 3) had smoking friends (+2.4). Youth without smoking friends (-0.8) and who considered smoking a risk factor for Covid-19 (-0.2) decreased their cigarette consumption.